CMS (Centre for Mawarith Studies): A New Pattern of Islamic Mawarith Education in Indonesia - Saiful Anwar; Samsirin Samsirin (At-Ta'dib, 2020)
In the recent decades, the implementation of “faraidh” in Indonesia is not as extensive as the study, the many cases of inheritance disputes that occur indicate that Islamic inheritance has not shown the life of the Muslim community in Indonesia. During such conditions, CMS (Center for Mawarith Studies) moved with new ideas in educating the science of faraidh. Its educational movement is not limited to schools but it is able to enter community institutions at the national and even international levels. This study aims to find out more about the CMS (Center for Mawarith Studies) thoughts and movements in educating Islamic inheritance in Indonesia. This study used a qualitative approach with a case study method at the Center for Mawarith Studies at Darussalam Gontor University. The results of the study concluded that the idea of CMS (Center for Mawarith Studies) education in Unida Gontor 1. The objective of Mawarits Learning was to build Mawarits Mind in families. 2. Determination before the distribution (PSP) is the basis for Mawarits educational viewpoint. 3. CMS (Center for Mawarith Studies) Where to Print Teachers, not Consultants. The CMS Unida Gontor educational movement includes 3 service programs 1. Mawarits School (SM) 2. Mawarits Call Center (MCC) 3. Mawarits Science Clinic (KIM). the textbook "Mawarits = PSP" (Determination Before the Distribution) series 1, 2 and 3. The learning method is the 3T "Tamtsili, Tashwiri, Tikrari". the teacher categories are mudarris, muallim and mudarrib. With this educational pattern, it is not an exaggeration if this educational movement is called a large movement in Islamic preaching as a struggle to strengthen and prosper Muslims.